IDENTIFIKASI JALUR PATAHAN AKTIF SUMATERA SEGMEN SEMANGKO (SUOH - KOTAAGUNG) MENGGUNAKAN METODE GEORADAR DAN GEOLISTRIK - , Basry Yadi Tang ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Conducted research on the identification of active fault pathways in Semangko segment, subsegment Suoh-Kotaagung, Lampung region, Sumatera. Georadar method with radar reflection profiling configuration and geoelectrical method with dipole-dipole configuration have been used in this research to determine the existence of fault pathways and the outlook subsurface structure which potentially indicate earthquake in this area. This research was conducted in 17 lines measurement divided to 4 subsegment of 10 subsegment in Kotaagung area, such as Asahan subsegment (2 lines), Sedayu subsegment (7 lines), Semangka subsegment (3 lines) and Kotaagung subsegment (5 lines). Reflexwave software has been used in georadar data processing obtained from the result of GSSI surveyor 20 measurement. There are five steps to process the data measurement, automatic gain control, static correction, bandpass filter, background removal, and migration to eliminate noise from the data in order to obtain radargram section. In addition, Earthimager 2DINV software has been used in geoelectrical processing data from the measurement of multichannel supersting R8. Inversion from apparent resistivity to actual resistivity has been conducted in this software used to interpret subsurface section in the research area. Identified fault pathways in this research have been indicated by line 3, 4, 5, and 6 in the sedayu subsegment, line 7 and 15 in Asahan subsegment, line 8, 9, and 14 in Kotaagung subsegment. The existence of fault subsegment were detected at shallow depth about 5-58 meter below surface area potentially indicate destructive earthquakes in the research area. Kotaagung subsurface structure is arranged by quartenary sediment, Sandy clay (0.1-80 ïm), and sand (100-500 ïm) that is separated by granite intrusion (600-100.000 ïm) indicating fault pathways